Old songs - Short, Charlotte Jane (My University, 1891)
Introduction: There is always a feeling of sadness which clings to a volume of old songs. The limp and faded leaves, and the torn and ragged edges are filled with memories of other days. Even though we may prize the old book and treasure the faint remembrance it possesses of others in days gone by the real spirit of the music may have fled. Should we try to sing and play those songs as others had done the same satisfaction would not be realized. The times our mothers sang us when we were rocked in the cradle and those we ourselves sang when we played at keeping house and sailor boy, now sound to us rather tame. Why? Is it that other and more cultivated tastes has left these old songs as memories of the past? Not entirely. I think some of these ancient melodies and their words are as stirring and sympathetic as though they had been written but yesterday. Such fine old strains as “Coming thro’ the Rye”, “Home, Sweet Home”, or, “Auld Lang Syne”’ will always find a place in the hearts of Americans, and will continue to live so long as we are a patriotic people.
Citation: Short, Charlotte Jane. Old songs. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Songs; Patriotism; American; Nostalgia; Music; Theses; Manuscripts (documents)